2004
DOI: 10.1037/0096-1523.30.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Location, Frequency Region, and Time Course of Selective Attention on Auditory Scene Analysis.

Abstract: Often, the sound arriving at the ears is a mixture from many different sources, but only 1 is of interest. To assist with selection, the auditory system structures the incoming input into streams, each of which ideally corresponds to a single source. Some authors have argued that this process of streaming is automatic and invariant, but recent evidence suggests it is affected by attention. In Experiments 1 and 2, it is shown that the effect of attention is not a general suppression of streaming on an unattende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
261
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(285 citation statements)
references
References 33 publications
22
261
2
Order By: Relevance
“…Somewhat different results were obtained by Cusack et al [24]. They presented thirty-three 10 s sequences of sounds with an ABA -ABA pattern, separated by gaps with durations of 1, 2, 5 or 10 s, selected in random order.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 87%
See 1 more Smart Citation
“…Somewhat different results were obtained by Cusack et al [24]. They presented thirty-three 10 s sequences of sounds with an ABA -ABA pattern, separated by gaps with durations of 1, 2, 5 or 10 s, selected in random order.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 87%
“…However, as pointed out by Moore & Gockel [28], the act of switching attention to the tone sequence may cause a re-setting of the build-up of stream segregation; the effect could be similar to what occurs when the characteristics of the sequence are changed suddenly, as described earlier. Indeed, using a task similar to that of Carlyon et al [26], Cusack et al [24] reported a re-setting of the build-up of stream segregation if attention was briefly diverted away from the ABA -ABA sequence presented to the left ear. As discussed by Cusack et al [24], it is not clear whether the re-setting occurred when attention was diverted away from the ABA -ABA sequence or when it was directed back to it from the different task.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 99%
“…It remains to be seen, whether this limit is rather small (e.g. similar, and perhaps even related to, the common limitation found for representations in short-term/working memory [34]) as was suggested by some studies [35] or can be large, provided that the concurrently active proto-objects are sufficiently distinct [36,37]. We discuss the issue of alternative sound representations further in §5.…”
Section: The Nature Of the Representations Underlying Sequential Groumentioning
confidence: 99%
“…one stream having higher saliency than the other, or being favoured by attentional selection) introduces a new level of competition within one of the already defined competitors. Thus, based on this notion, competition occurs hierarchically, as in the hierarchical decomposition model proposed by Cusack et al [36].…”
Section: Multi-stable Perception Through Competitionmentioning
confidence: 99%
See 1 more Smart Citation